Final Program Data and Factors Associated With Long-Acting Reversible Contraception Removal: The Zika Contraception Access Network. Issue 5 (May 2020) - Lathrop, Eva; Hurst, Stacey; Mendoza, Zipatly; Zapata, Lauren B.; Cordero, Pierina; Powell, Rachel; Green, Caitlin; Moreno, Nilda; Jamieson, Denise J.; Romero, Lisa
Abstract : OBJECTIVE: To describe characteristics of the full population of women who participated in the Zika Contraception Access Network program in Puerto Rico during the virus outbreak and to examine factors associated with removal of a long-acting reversible contraception (LARC) method by a Zika Contraception Access Network provider during the program's duration (May 2016–September 2017). METHODS: We conducted an observational cohort study. The Zika Contraception Access Network program was designed to increase access to contraception services in Puerto Rico for women who chose to prevent pregnancy during the Zika virus outbreak as a primary strategy to reduce adverse Zika virus–related pregnancy and birth outcomes. Among program participants, an observational cohort of women served by the Zika Contraception Access Network Program, we describe their demographic and program-specific characteristics, including contraceptive method mix before and after the program. We also report on LARC removals by Zika Contraception Access Network providers during the program. We examined factors associated with LARC removal using multivariable logistic regression. RESULTS: A total of 29, 221 women received an initial Zika Contraception Access Network visit during the program. Ninety-six percent (27, 985) of women received same-day provision of a contraceptive method and 70% (20, 381) chose a LARC method. While the program was active, 719 (4%) women who chose a LARC at the initial visit had it removed. Women with a college degree or higher were more likely to have their LARC removed (adjusted prevalence ratio [aPR] 1.24); breastfeeding women (aPR 0.67) and those using a LARC method before Zika Contraception Access Network (aPR 0.55) were less likely to have their LARC removed. CONCLUSION: The Zika Contraception Access Network program was designed as a short-term response for rapid implementation of contraceptive services in a complex emergency setting in Puerto Rico and served more than 29, 000 women. The Zika Contraception Access Network program had high LARC uptake and a low proportion of removals by a Zika Contraception Access Network provider during the program. A removal-inclusive design, with access to removals well beyond the program period, maximizes women's reproductive autonomy to access LARC removal when desired. This model could be replicated in other settings where the goal is to increase contraception access. Abstract : The Zika Contraception Access Network increased access to contraception in the context of a public health emergency in Puerto Rico.